Brucellosis due to Brucella suis in a swine herd associated with a human clinical case in the State of São Paulo, Brazil - Meirelles-Bartoli, Raphaella Barbosa; Mathias, Luis Antonio [UNESP]; Ernesto Samartino, Luis (Springer, 2012)
Brucella suis has been recognized as the major etiological agent of human brucellosis in areas free from Brucella melitensis infection. However, with changes in swine management, the occurrence of swine brucellosis has decreased as has the human incidence of B. suis infection. A swine brucellosis outbreak within a herd from Jaboticabal (So Paulo, Brazil) was detected in July 2006. The herd comprised approximately 300 sows and 1,500 finishing animals. Many sows within this herd experienced abortions, while others exhibited vaginal discharge; three sows suffered posterior paralysis. Among 271 sows, 254 (93.7%) tested positive for brucellosis by complement fixation, and among 62 randomly bled finishing animals, 17 (27.4%) also tested positive. The B. suis biovar 1 was cultured from 14 aborted fetuses and six sows. Brucella was identified using routine methods. Fourteen farm workers were tested using agglutination tests, with three workers showing evidence of Brucella antibody titers. A 39-year-old woman, who worked with maternal pigs and had direct contact with aborted fetuses, presented an agglutinating titer of 480 IU/mL and displayed clinical signs of infection. Our findings suggest that despite a reduction of swine brucellosis throughout Brazil, B. suis infection still occurs, thereby posing a zoonotic risk.
Keywords: Swine brucellosis outbreak; Brucella suis infection in humans; Clinical signs; Routine methods; Brucella growth